IMPROVING SCHOOL ENGAGEMENT STUDENT WITH AUTISM SPECTRUM DISORDER USING FLIP-THROUGH AND FOLLOW METHOD IN SOCIAL STORY AND VISUAL SCHEDULE - Rizka Ramadhani Savira Tatyagita; Dewi Retno Suminar, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The aim of this study is to investigate the effectiveness of Flip-through and Follow method for students with Autism Spectrum Disorder (ASD). The research is being conducted by applying Flip-through and Follow method for students with autism to improve school engagement. School engagement is active participation of the student in the academic and non-academic area which is being assessed through behavioral, emotional and cognitive engagement. Flip-through and Follow Method is an intervention that combines social story and visual schedule. Social Story is a short story which can support individuals with autism to comprehend social situations. Visual Schedule is a visual representation of a daily agenda or a sequence of task or activity to be followed. The visual schedule will be tucked in the story as the social story ads information about why they should behave appropriately during school activities. This research is conducted using multiple baseline designs across conditions. The participant in this research is an elementary school-aged child, diagnosed with mild autism, having difficulties engaging with school activities and able to communicate verbally. The data will be collected using an observation form written by the author adjusted for school engagement for a student with autism. Data will be analyzed using a descriptive statistic and Wilcoxon T-Test. The result shows that Flip-through and follow method is not entirely effective in improving school engagement. Flip-through and follow is effective in improving engagement in classroom learning activities and scout activities, however flip-through and follow is less effective in improving physical education activity.